International Monetary Fund Annual Report 1999. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
Annual Report of the Executive Board for the financial year ended April 30, 1999.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet